2006
DOI: 10.1021/ac060044b
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for Pressurized Planar Electrochromatography in a Completely Closed System

Abstract: Pressurized planar electrochromatography (PPEC) is the mode which offers much higher separation efficiency in comparison to conventional planar chromatography, including both higher performance and much higher speed of separation. In this paper, we present a new device for performing PPEC in which the whole area of the chromatographic plate is pressurized. Both electrodes (anode and cathode) are washed with the mobile phase during the experiment, which prevents gas bubbles from collection in the region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 21 publications
8
43
1
Order By: Relevance
“…Electroosmosis is used to drive the mobile phase flow through the layer in pressurized planar electrochromatography and requires an aqueous buffer as a component of the mobile phase [23,[57][58][59][60][61][62]]. An electric field applied across the layer is used to control the mobile phase velocity which is independent of the solvent front migration distance.…”
Section: Pressurized Planar Electrochromatographymentioning
confidence: 99%
“…Electroosmosis is used to drive the mobile phase flow through the layer in pressurized planar electrochromatography and requires an aqueous buffer as a component of the mobile phase [23,[57][58][59][60][61][62]]. An electric field applied across the layer is used to control the mobile phase velocity which is independent of the solvent front migration distance.…”
Section: Pressurized Planar Electrochromatographymentioning
confidence: 99%
“…[19] Other devices for PPEC were designed by our group. [15,16] Our first construction for PPEC was based on a commercially available horizontal DS chamber for TLC. [15] The next device was a quite new construction which is schematically presented in Figure 3.…”
Section: Devices For Ppecmentioning
confidence: 99%
“…[15] The next device was a quite new construction which is schematically presented in Figure 3. [16] A prewetted chromatographic plate with the adsorbent layer face down is horizontally positioned in the chamber and is completely covered by a teflon foil and silicon sheet, which are pressed to the adsorbent layer by plastic and metal blocks. Special troughs beneath the adsorbent layer situated on both sides of the chromatographic plate are used for mobile phase delivery to the chromatographic plate.…”
Section: Devices For Ppecmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nurok [6] and Dzido et al [7] made comprehensive reviews on recent progress of PEC, which demonstrated its advantages of improved resolution and efficiency compared to conventional planar chromatography. Although good separation of dyes was obtained in RP PEC mode [5], the excessive evaporation of mobile phase in open surrounding and the accumulation of solutes on stationary phase resulted in poor reproducibility.…”
Section: Introductionmentioning
confidence: 99%